Análise socioespacial de egressos da EFA Puris de Araponga, Minas Gerais - Eli Perpétuo Duarte Ferreira (2024)
The present study analyzed, as of the perceptions of egresses rural youth from 2010 to 2020, the received formation at Família Agricola Puris school of Araponga, Minas Gerais, and the professional and/ or productive insertion of them into the work world, traduced at socio-spatial Mobility scope. For that, a study of case was done involving three strategies of search: bibliographic, documental and field survey. Bibliographic research allowed the elaboration of a theoretical construction about the topic, fundamental for the discussion about the results. The documental researches dedicate to the knowledge of Família Agricola Puris school and of her technical course integrated with High school in agriculture and livestock. Finally, the field survey allowed to analyze, as of the perceptions of egresses rural youth, the meaning of the received formation at socio-spatial mobility scope. For that a semi-structured questionnaire was applied to a non-probabilistic sample of graduates. More than that, interviews with community leadership of Família Agricola Puris school were made for complementary information. 28 egresses and five community leaderships participated. From the analysis of the responses, organized in graphs and charts, ally the data collected together with the leaderships, is possible to observe that the lack of opportunities, help, property and Investments are problems that make interference at the decision of the egresses to stay or not at the region of origin. On the other hand, concludes that of Família Agricola Puris school, through the alternance pedagogy and your pedagogics instruments enables to rural youth access to comprehensive formation, citizenship construction, autonomy in the form of protagonism, improve the territory, besides the possibility of perceiving and seeking places where the youth desire to be.